The Toxicity Of Brachiaria Detimbens - Mohamed Mustapha, Noordin (1988)
Nine healthy adult Indigenous Sheep of Malaysia (ISM) of which four were rumen fistulated were allowed to graze on a hactare of pure stands of Brachiaria decumbens. The animals developed signs of photosensitization, jaundice, and even death within three to four weeks. Occasionally signs pertaining to nervous dysfunction and submandibular edema were also observed. By the end of the ninth week there were no survivors. Their serum AST, GLDH, BUN, creatinire, bilirubin (total and direct) rose prcgressively thru:ghout the entire period of study. There was evidence of neutroIililic leucocytosis with the absence of toxic neutrophi is and the absence of haemolyticcris is in the intoxicated animals. Rumina l stasis occurred approximately three weeks postgrazirg. The gross, histolcgical and ultrastructural charges in the livers and kidneys indicated presence of necrosis and degeneration. Three healthy adult rumen fistulated Australian Milking Zebu (ALT) bulls fed decumbens for nine weeks did not develop any evidence of toxicosis either clinically or clinicopathologically as that seen in the sheep.